2018
DOI: 10.21307/pm-2018.57.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges of Veterinary Microbiological Diagnostics Concerning the Susceptibility of Staphylococci to Antibiotics

Abstract: Staphylococci belong to bacteria often isolated from clinical material obtained from animals. Unlike in human medicine, in veterinary, different species of coagulase-positive staphylococci are isolated from clinical specimens, and except Staphylococcus aureus, Staphylococcus pseudintermedius, and other species are also often recognized. Recently, the taxonomy of staphylococci has been updated, therefore, now it is necessary to recognize the new species as well. Currently, coagulase-negative staphylococci are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Methicillin-resistant Staphylococcus aureus (MRSA) infection can only be treated with limited antibiotics and needs long-term treatment ( 163 , 165–167 ). MRSA infection is zoonotic ( 168 ), and continuous antimicrobial susceptibility surveillance is very crucial to control the transmission of this strain from animal production to humans and vice versa ( 169 ). They may transfer resistance traits to S. aureus or other bacteria, resulting in the emergence of multidrug-resistant strains ( 94 , 135 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) infection can only be treated with limited antibiotics and needs long-term treatment ( 163 , 165–167 ). MRSA infection is zoonotic ( 168 ), and continuous antimicrobial susceptibility surveillance is very crucial to control the transmission of this strain from animal production to humans and vice versa ( 169 ). They may transfer resistance traits to S. aureus or other bacteria, resulting in the emergence of multidrug-resistant strains ( 94 , 135 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
“…Antimicrobials are an important tool in mastitis control programs; therefore, surveillance of antimicrobial susceptibility is important to ensure optimal results when using them and minimize the risk of resistance (Bowler et al 2020 ; Kizerwetter-Świda et al 2018 ). Staphylococci can express resistance to a range of antimicrobials, of which methicillin resistance is of public health concern (Crespi et al 2022 ; Fergestad et al 2021 ).…”
Section: Non- Aureus Staphylococci and Mammaliicoccimentioning
confidence: 99%
“…Infections caused by methicillin-resistant Staphylococcus (MRS) are more damaging due to the long-term treatments and limited drug options (Adkins et al 2018b ; Crespi et al 2022 ; Mahato et al 2017 ; Virdis et al 2010 ). Recent reports from different parts of the world revealed that MRS are an emerging cause of infection and a potent threat to the dairy industry and public health due to their zoonotic potential (Kizerwetter-Świda et al 2018 ; Windria et al 2016 ). The increased exposure to drugs and the use of antimicrobials in animal diseases represents a danger to human health whose impact and effect are not yet well characterized but may lead to the emergence of antimicrobial-resistant strains, which makes antimicrobial susceptibility surveillance very crucial (Persson et al 2011 ).…”
Section: Non- Aureus Staphylococci and Mammaliicoccimentioning
confidence: 99%